Chronic suppurative otitis media, middle ear pathology and corresponding hearing loss in a cohort of Greenlandic children. (April 2016) - Avnstorp, Magnus Balslev; Homøe, Preben; Bjerregaard, Peter; Jensen, Ramon Gordon
Abstract: Background: Otitis media (OM) has been observed at elevated prevalence rates in Greenlandic children. OM associated hearing loss (HL) may compromise the children's linguistic skills, social development and educational achievements. Objectives: We investigated the prevalence of chronic suppurative otitis media (CSOM), otitis media with effusion (OME) and tympanic membrane sequelae of OM, and compared the corresponding hearing thresholds. Methods: In 2010 we examined a cohort of 223 Greenlandic children aged 4–10 years by video otoscopy, tympanometry and tested hearing thresholds for the low-frequencies: 500, 1000 and 2000 Hz and the high-frequencies: 4000 and 6000 Hz. HL was categorized according to the worst hearing ear and was compared within the groups: CSOM, OME, tympanic membrane sequelae of OM and normal. Results: Of 207 children, 5.8% had CSOM, 13.9% had OME and 55.6% had tympanic membrane sequelae of OM. The median pure tone average in low-frequencies/high-frequencies were: CSOM: 34.2/31.3 dB, OME: 23.3/22.5 dB, Sequelae of OM: 13.3/15 dB and normal ears: 11.7/12.5 dB. We found a significant difference ( p  < 0.05) between the four groups. In 56.5% of all children a HL > 15 dB in any frequency was found, while 6.5% suffered from a bilateral low-frequency HL > 25 dB. Conclusion: The severity of OM significantly corresponded to increased HL. The burden of CSOM and HL remains high in young Greenlandic children. Aggressive treatment with antibiotics, improved hearing rehabilitation, sound field amplification in classrooms and otosurgical capacity should be further promoted in Greenland.